Navigating Crisis: The Dynamics of Global Communication Response in Indonesia (Universitas Terbuka, 2024)
This study examines the complexities of crisis communication in the context of Indonesia, considering the nation’s vulnerability to a range of crises, such as health problems, political upheaval, and natural catastrophes. Using a mixed-methods approach, the study combined social network analysis, surveys, content analysis, and qualitative interviews to give a thorough knowledge of the dynamics of crisis communication.Important conclusions emphasize the important of social media and other international communication channels to coordinate crisis response and speedy information distribution. However, obstacles, e.g., the dissemination of false information, highlight the need for stronger approaches to information management. Furthermore, the practices of crisis communication in Indonesia are heavily influenced by contextual, social, and cultural aspects. Communication is influenced by language diversity, cultural standards, and religious sensitivity techniques, highlighting the significance of cultural sensitivity and comprehension of regional situations. The findings have implications for stakeholders, practitioners, and policymakers who are active in communication and crisis management. Enhancing public education and awareness campaigns, strengthening international cooperation to fortify crisis response skills, and boosting coordination among government institutions are among the recommendations. Although the study offers insightful information about crisis communication in Indonesia, it is important to recognize its limits and the dynamic character of crisis communication to guide future research efforts. The overall goal of this research is to contribute to the development of better crisis management and resilience building techniques in Indonesia and beyond.